When Do Employees Speak Up Under Job Stressors? Exploring the Potential U-Shaped Relationship Between Hindrance Stressors and Voice Behavior - Zhou, Longzhi; Yang, Kejian; Wang, Zhen; Luo, Zhengxue (Frontiers in Psychology, 2019)
Drawing upon the conservation of resources theory, we intend to examine the relationships between voice behaviors and job stressors. Specifically, we propose a nonlinear relationship between hindrance stressors and prohibitive and promotive voice behaviors. Furthermore, we argue that challenge stressors moderate the nonlinear relationship between hindrance stressors and voice behaviors. Based on a sample of 361 employees in China, our results indicate that the relationship between hindrance stressors and prohibitive and promotive voice is U-shaped. The relationships between challenge stressors and prohibitive and promotive voice are linearly positive. Moreover, challenge stressors moderate the relationships between hindrance stressors and voice behaviors, thus, when challenge stressors were high, hindrance stressors are negatively linear related to prohibitive & promotive voice behaviors, and when challenge stressors are low, hindrance stressors are curvilinearly related to prohibitive and promotive voice behaviors. The theoretical and practical implications of these results are discussed.